Resilience theory: a framework for engaging urban design - Cunningham, Kevin L. (Kansas State University, 2013)
Landscape architects are challenged with finding appropriate solutions to adequately address the dynamic nature of urban environments. In the 1970's C.S. Holling began to develop resilience theory, which is intended to provide a holistic understanding of the way socio-ecological systems change and interact across scales. Resilience theory addresses the challenges and complexities of contemporary urban environments and can serve as a theoretical basis for engaging urban design practice. To test the validity of resilience theory as a theoretical basis for urban design, this thesis is an exploration of the addition of resilience theory to current landscape architecture literature and theory through a three-part methodology: a literature review that spans a breadth of research, case study analyses, and an application of resilience theory through a design framework in two projective design experiments. The resilience framework bridges between complex theory and design goals/strategies in a holistic approach. Through the identification of key connections in the reviewed literature that situate the relevance of resilience theory to landscape architecture and the subsequent case study analysis, specific methods for applying resilience theory to urban design practice are defined within the proposed framework. These methods fit within five main categories: identify and respond to thresholds, promote diversity, develop redundancies, create multi-scale networks and connectivity, and implement adaptive planning/management/design practices. The framework is validated by the success of the projective design application in the winning 2013 ULI/Hines Urban Design Competition entry, The Armory. Resilience theory and the proposed design framework have the potential to continue to advance the prominence of landscape architecture as the primary leader in urban design practice.
Keywords: Resilience Theory; Resilience; Landscape Architecture; Urban Design; Landscape Architecture (0390)